MARITAL STATUS AND PERFORMANCE OF WOMEN’S FAMILY BUSINESSES IN BURKINA FASO - Sankara , Aminata Traoré; Kaboré-Kanazoé , Issouf (Journal of Allied Research in Management and Entrepreneurship (JARME), 2024)
The vitality of family businesses (FBs) holds substantial importance in driving the development of countries, particularly in developing regions. This study delves into the significance of FBs within the context of the European, American, Asian, Sub-Saharan African, and Middle Eastern economies. These enterprises represent a significant majority in these economic landscapes, comprising approximately 95% of businesses in Sub-Saharan Africa and the Middle East. Moreover, there is a consensus among various studies that FBs tend to outperform other enterprise types. Firm performance, being a multidimensional construct, encompasses various dimensions such as the social, economic, political, and systemic aspects. However, a consensus on performance indicators is yet to be reached. This paper addresses the complexities of measuring the performance of FBs, taking into consideration indicators like revenue growth, value added, earnings before interest and taxes depreciation and amortization, earnings before interest and taxes, net operating income, and net profit.